Teachers’ beliefs about multilingual students and their language choice: exploring the effect of language hierarchies - Bosch, Jasmijn; Doedel, Jet (Dutch Journal of Applied Linguistics, 2024)
This study investigated Dutch primary school teachers’ attitudes towards multilingualism and whether their beliefs are influenced by the social prestige of the languages involved. Using an online questionnaire, we investigated to what extent teachers are concerned about Dutch language development of child L2 learners, what they would advise parents, how they respond to home language use in the classroom and the schoolyard, and whether teachers’ responses are influenced by language hierarchies (i.e., are there any differences between attitudes towards a French child called Emile speaking French, or a Pakistani child called Mohamed speaking Urdu?). Our results showed great individual variation in teachers’ attitudes, but no effects of language status. Moreover, teachers with more multilingual students in their class and teachers who had received training on multilingualism were more likely to accept L1 use at school, while the proportion of multilingual students was negatively related to teachers’ concerns about L2 development.